Beryllium solubility and hydrolysis in dilute to concentrated CaCl2 solutions: thermodynamic description in cementitious systems - Çevirim-Papaioannou, Nese; Androniuk, Iuliia; Miron, George Dan; Altmaier, Marcus; Gaona, Xavier (Frontiers in Nuclear Engineering, 2023)
The solubility and hydrolysis of Be(II) was investigated from undersaturation conditions in alkaline, dilute to concentrated CaCl2 solutions (0.05–3.5 M). Experiments were performed with α-Be(OH)2(cr) under Ar atmosphere at T = (22 ± 2)°C. Aqueous Be speciation was further investigated by means of molecular dynamics (MD) calculations. For the most diluted CaCl2 systems (0.05 and 0.25 M), a solubility minimum is observed at pHm ≈ 9.5 {with [Be(II)] ≈ 10−7 M}, consistent with solubility data previously reported in NaCl and KCl solutions. Above this pHm, and at higher CaCl2 concentrations, a steep increase in the solubility with a slope of ∼ +2 is observed, hinting towards the predominance of the moiety [Be(OH)42–] in the aqueous phase. In NaCl and KCl systems, this hydrolysis species prevails only above pHm ∼ 13, thus supporting the formation of ternary complex/es Ca–Be(II)–OH(aq) in CaCl2 solutions. The analysis of solubility data in combination with MD calculations underpin the key role of the complex Ca2[Be(OH)4]2+ in alkaline to hyperalkaline systems containing Ca. In combination with our previous work in NaCl–NaOH and KCl–KOH systems, complete chemical, thermodynamic and (SIT) activity models are derived for the first time for the system Be2+–Ca2+–Na+–K+–H+–Cl––OH––H2O(l). This model provides an accurate and robust tool for the evaluation of Be(II) solubility and speciation in a diversity of geochemical conditions, including source term calculations of beryllium in the context of repositories for nuclear waste disposal with a high cement inventory.